2004
DOI: 10.1128/jvi.78.6.2674-2681.2004
|View full text |Cite
|
Sign up to set email alerts
|

Binding to Decay-Accelerating Factor Is Not Required for Infection of Human Leukocyte Cell Lines by Enterovirus 70

Abstract: Enterovirus 70 (EV70) is one of several human enteroviruses that exhibit a propensity for infecting the central nervous system (CNS). The mechanisms by which neurotropic enteroviruses gain access to and invade the CNS are poorly understood. One possibility is that circulating leukocytes become infected and carry neurotropic enteroviruses to the CNS. We examined the ability of EV70 to infect cell lines derived from lymphoid, myeloid, and monocytic lineages. Most leukocyte cell lines tested bound radiolabeled EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
2
16
1
Order By: Relevance
“…The other serotypes of HEV-D (EV68 and EV70) use DAF as a receptor in HeLa cells (Karnauchow et al, 1996;Blomqvist et al, 2002). EV70 also uses sialic acid-containing receptors in a variety of other human cell lines (Alexander & Dimock, 2002;Haddad et al, 2004;Nokhbeh et al, 2005). Our results suggest that EV94 does not need DAF to infect RD cells.…”
Section: Discussionsupporting
confidence: 52%
“…The other serotypes of HEV-D (EV68 and EV70) use DAF as a receptor in HeLa cells (Karnauchow et al, 1996;Blomqvist et al, 2002). EV70 also uses sialic acid-containing receptors in a variety of other human cell lines (Alexander & Dimock, 2002;Haddad et al, 2004;Nokhbeh et al, 2005). Our results suggest that EV94 does not need DAF to infect RD cells.…”
Section: Discussionsupporting
confidence: 52%
“…As this inflammatory disease of the subarachnoid space is common to most EV serotypes, it is assumed that viruses travel through the blood, breaching the blood-CSF barrier either directly or through infected leukocytes. A number of studies showed that PV, CV-B3 and EV-A71 could infect various immune cells (Eberle et al, 1995;Vuorinen et al, 1996;Haddad et al, 2004;Wahid et al, 2005a, b;Tabor-Godwin et al, 2010). These data suggest a role of infected leukocytes in EV dissemination to the CNS through a 'Trojan horse' process.…”
Section: Introductionmentioning
confidence: 93%
“…Previously, we demonstrated that the glycosyl phosphatidylinositol (GPI)-linked protein CD55 plays a major role in EV70 binding to, and infection of, HeLa cells (35,36). However, EV70 attachment to all other human cell lines that we have tested was CD55 independent but required sialic acid, as determined by sensitivity to Vibrio cholerae sialidase, and sialidase treatment of HeLa cells also reduced EV70 binding (1,28). Like EV70, both adenovirus 37 and some avian influenza A viruses, in particular H7 subtypes, are associated with eye infections (4,5,13,24,39,64).…”
mentioning
confidence: 99%